Respuesta :

Answer:

x = 0

Step-by-step explanation:

2(x+7) 2x + 20 - 2 = x+4(2x + 8) start by distributing

2(x+7) would be 2x+14

4(2x+8) would be 8x+32

2x+14 x 2x + 20 - 2 = x + 8x + 32 now combine like terms

2x and 2x can be combined on the left side

x and 8x can be combined on the right side

4x + 14 + 20 - 2 = x + 8x + 32

4x + 32 = 9x + 32 you can now solve this equation

start by subtracting 4x on both sides

32 = 5x +32 now subtract 32 on both sides

0 = 5x so x = 0

Answer:

x = 0

2(x+7) 2x + 20 - 2 = x+4(2x + 8) start by distributing

2(x+7) would be 2x+14

4(2x+8) would be 8x+32

2x+14 x 2x + 20 - 2 = x + 8x + 32 now combine like terms

2x and 2x can be combined on the left side

x and 8x can be combined on the right side

4x + 14 + 20 - 2 = x + 8x + 32

4x + 32 = 9x + 32 you can now solve this equation

start by subtracting 4x on both sides

32 = 5x +32 now subtract 32 on both sides

0 = 5x so x = 0

ACCESS MORE